More answers

Simplifying -3(-x-2) would involve distributing the -3 to both terms inside the parentheses. This gives us 3x + 6 as the simplified expression.

Q: What is -3(-x-2) simplified?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

13

In algebra and mathematics the simple above equation can be written and simplified as follows . (5x2 8x)-(3x2-x) = 10 + 8x -6 +x = 4 +7x.

7

3x2 times x-33 can be simplified to: 3x3 times -27

the answer is 3x2

Related questions

13

It is an expression that can be simplified to: 4x2-42

In algebra and mathematics the simple above equation can be written and simplified as follows . (5x2 8x)-(3x2-x) = 10 + 8x -6 +x = 4 +7x.

7

3x2 times x-33 can be simplified to: 3x3 times -27

12x4 - 3x2 cannot be simplified because the different exponents says that they are not like terms

9x+3x2=14+x-1 AND 2x2+x2+x=30

3x2-y=6 3x2-y=6

The sum 6 (3x^2) + 8x -3 plus 3 (3x^2) - 7x + 2 = 27 x^2 + x -1

6x^2 +32x +12 -4x -3x^2 -36 = 3x^2 +28x -24 simplified

While it is possible to factor 3x2 from both of these and get 3x2(4 - 1), it's a lot easier to subtract 3x2 from 12x2 and get 9x2

3x2-27 is equal to -21.